Progression of Interstitial Lung Disease in Systemic Sclerosis: The Importance of Pneumoproteins Krebs von den Lungen 6 and CCL18. Issue 12 (1st November 2019) - Volkmann, Elizabeth R.; Tashkin, Donald P.; Kuwana, Masataka; Li, Ning; Roth, Michael D.; Charles, Julio; Hant, Faye N.; Bogatkevich, Galina S.; Akter, Tanjina; Kim, Grace; Goldin, Jonathan; Khanna, Dinesh; et al.
Abstract : Objective: To investigate the relationship between Krebs von den Lungen 6 (KL‐6) and CCL18 levels and the severity and progression of systemic sclerosis (SSc)–related interstitial lung disease (ILD). Methods: Patients enrolled in the Scleroderma Lung Study II (cyclophosphamide [CYC] versus mycophenolate mofetil [MMF]) were included. Baseline and 12‐month plasma samples were analyzed by enzyme‐linked immunosorbent assay to assess CCL18 and KL‐6 levels. The forced vital capacity (FVC) and the diffusing capacity for carbon monoxide (DLco ) were measured every 3 months. Joint models were created to investigate the relationship between baseline CCL18 and KL‐6 levels and the course of the FVC and DLco over 1 year according to treatment arm. Results: Baseline KL‐6 and CCL18 levels each correlated with the extent of radiographic fibrosis. Levels of both CCL18 and KL‐6 declined significantly at 1 year. In both treatment arms (n = 71 for CYC, n = 62 for MMF), a higher baseline KL‐6 level predicted progression of ILD based on the course of FVC ( P = 0.024 for CYC; P = 0.005 for MMF) and DLco ( P < 0.001 for CYC; P = 0.004 for MMF) over 1 year. A higher baseline CCL18 level predicted progression of ILD based on the course of the FVC ( P < 0.001 for CYC; P = 0.007 for MMF) and DLco ( P = 0.001 for CYC; P < 0.001 for MMF) over 1 year, as well as mortality ( P = 0.0008 for CYC arm only). Conclusion: In a rigorously conducted clinical trial for SSc‐related ILD, KL‐6 and CCL18 levels correlated with ILD severity and declined with immunosuppression. Patients with higher baseline KL‐6 and CCL18 levels were more likely to experience disease progression despite treatment. KL‐6 and CCL18 levels could be used to identify patients with a progressive ILD phenotype who may benefit from a more aggressive initial treatment approach.